Is the Effect of Compulsory Community Treatment on Preventable Deaths from Physical Disorders Mediated by Better Access to Specialized Medical Procedures?. (January 2014) - Kisely, Steve; Xiao, Jianguo; Lawrence, David; Jian, Le
Objectives: Compulsory community treatment has been shown to reduce preventable deaths from physical disorders—these causes being up to 10 times more common than suicide in psychiatric patients. We investigated whether this was mediated by better access to specialized medical procedures. Method: All patients on compulsory community treatment for over 11 years were compared with matched control subjects using linked administrative health data from Western Australia (state population of about 2.24 million). Outcomes were access to revascularization and other specialized procedures at 1-, 2-, and 3-year follow-up. Logistic regression was used to adjust for demographics, prior health service use, diagnosis, and length of psychiatric history. Results: There were 2757 patients and 2687 control subjects (total n = 5444). Sixty-five per cent were males ( n = 3522), and the average age was 36 years (SD 13.2). Most had schizophrenia or other nonaffective psychoses (74%), followed by affective disorders (26%). At 2-year follow-up, 2% ( n = 53) of patients and 2.6% ( n = 69) of control subjects had undergone a specialized intervention. Compulsory community treatment did not result in greater access to specialized procedures at all 3 time points even after adjusting for potential confounders. Conclusions: Greater access to specialized procedures does not explain the reduced mortality from preventable physical illness that had been reported in patients on community treatment orders. There must be other explanations for this finding, such as mental health staff facilitating access to chronic disease management in primary care. This warrants further research.